THE EFFECT OF PROFITABILITY, CAPITAL STRUCTURE, AND IMPLEMENTATION OF CORPORATE GOVERNANCE MECHANISM ON FIRM VALUE - Rina Hartanti; fahri yulandani; M Rizky Riandi (Jurnal Akuntansi Trisakti, 2019)
The purpose of this study is to explain the effect of Profitability, Capital Structure, and the application of Good Corporate Governance to Firm Value. The population of the study includes companies registered in the LQ-45 which are listed on the Indonesia Stock Exchange for the period 2015-2017. The technique of determining the sample used is purposive sampling. This study uses a multiple linear regression approach. Based on the results of testing, this study proves that profitability, capital structure, and the application of the GCG mechanism together affect firm value. This study also proves that partially profitability proxied by ROA and Managerial Ownership has a positive effect on Firm Value. The results showed that capital, which is proxied by DER and GCG, which is proxied by Institutional Ownership, does not have a positive effect on Corporate Value